Effects of an alginate-containing variable-viscosity enteral nutrition formula on defecation, intestinal microbiota, and short-chain fatty acid production. (April 2020) - Mizuno, Hideaki; Bamba, Shigeki; Abe, Nobutsugu; Sasaki, Masaya
Graphical abstract: Highlights: The alginate-containing variable-viscosity liquid formula improved stool form. This formula lowered fecal pH and increased blood short-chain fatty acid. The benefit of this formula could be mediated by the fermentation of alginate. Abstract: This study aimed to elucidate the effects of a liquid polymeric formula containing alginate, a source of water- soluble dietary fiber, on stool form, intestinal microbiota, and the production of short-chain fatty acid production. Participants were 11 elderly patients with malnutrition and poor oral intake, who required enteral feeding. The alginate-containing liquid formula, which characteristically changes state from liquid to semi-solidified depending on pH, was administered for 4 weeks. This variable-viscosity liquid formula significantly improved the values of nutritional indices and stool form. Analysis of fecal specimens revealed significant decreases in pH. The concentrations of short-chain fatty acids did not change significantly in stool samples, but acetic acid and propionic acid were significantly increased in blood samples. The proportion of Clostridium cluster XI in fecal microbiota was also significantly increased. The alginate-containing variable-viscosity liquid formula significantly improved stool form, lowered fecal pH, and short-chain fatty acid concentrations in blood.